Development of Quizizz-Based Interactive Questions to Measure Scientific Reasoning Skills - Malik, Adam; Setiawan, Yusuf; Setya, Winda (Jurnal Pendidikan Fisika dan Keilmuan (JPFK), 2021)
This study aims to determine the feasibility level, students' scientific reasoning abilities, and students' responses to the use of quizizz-based interactive questions in measuring students' scientific reasoning skills. This research method uses the 4D model (Define, Design, Development, and Dissemination). The results showed that quizizz-based interactive questions to measure scientific reasoning skills developed were declared very feasible by the validators at a percentage of 82.6%. The results of the percentage of students' scientific reasoning skills on conservation reasoning indicators are 25%, probabilistic reasoning 20.83%, proportional reasoning 8.33%, correlation reasoning 4.17%, variable reasoning 8.33%, and hypothesis-deductive reasoning 12.50 %. The question has positive response criteria as seen from the results of the assessment of students by 88% with very interesting interpretations. Thus, it can be concluded that quizizz-based interactive questions to measure scientific reasoning skills are very feasible to use and get a positive response from students.